Curcumin and Kolaviron Ameliorate Di-n-Butylphthalate-Induced Testicular Damage in Rats (2007)
The present study was carried out to evaluate the ameliorative effects of kolaviron (a biflavonoid from the seeds of Garcinia kola) and curcumin (from the rhizome, Curcuma longa L.) on the di-n-butylphthalate (DBP)-induced testicular damage in rats. Administration of DBP to rats at a dose of 2 g/kg for 9 days significantly decreased the relative testicular weights compared to the controls, while the weights of other organs remained unaffected. Curcumin or kolaviron did not affect all the organ weights of the animals. While only DBP treatment significantly increased the testicular malondialdehyde level and gamma-glutamyl transferase activity (γ-GT), it markedly decreased glutathione level, the testicular catalase, glucose-6-phosphate dehydrogenase, superoxide dismutase, sperm γ -GT activities and serum testosterone level compared to the control group. Data on cauda epididymal sperm count and live/dead ratio were not significantly affected in the DBPtreated rats. Alone, DBP treatment resulted in a 66% decrease in spermatozoa motility and a 77% increase in abnormal spermatozoa in comparison to control. DBP-treated rats showed marked degeneration of the seminiferous tubules with necrosis and defoliation of spermatocytes. The DBP-induced injuries in biochemical, spermatological parameters and histological structure of testis were recovered by treatment with kolaviron or curcumin. The pattern in the behaviour of these compounds might be correlated with their structural variations. Our results indicate that kolaviron and curcumin protect against testicular oxidative damage induced by DBP. The chemoprotective effects of these compounds may be due to their intrinsic antioxidant properties and as such may prove useful in combating phthalate-induced reproductive toxicity.